PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMAN 8 KOTA BEKASI - Indriyanto, Bagus; Siahaan, Matdio; Anas, Haryudi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Teacher performance is a determining factor in students' success in understanding the material, so improving teacher quality is a priority in developing the quality of education. The type of research used in this study is quantitative research. The sampling technique employed is non-probability sampling using a saturated sample (census) method, in which all members of the population were used as the sample, totaling 70 teachers at SMAN 8 Kota Bekasi. The data analysis method used is multiple linear regression. The data was processed using IBM SPSS Statistics Version 26. The results of this study show that (1) Leadership style has a negative and insignificant partial effect on the performance of teachers at SMAN 8 Kota Bekasi, (2) The work environment has a negative and insignificant partial effect on the performance of teachers at SMAN 8 Kota Bekasi, (3) Leadership style and work environment have a simultaneous or joint effect on the performance of teachers at SMAN 8 Kota Bekasi